2014
DOI: 10.1186/1476-4598-13-127
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor miR-24 restrains gastric cancer progression by downregulating RegIV

Abstract: BackgroundmicroRNAs are small noncoding RNAs that modulate a variety of cellular processes by regulating multiple targets, which can promote or inhibit the development of malignant behaviors. Accumulating evidence suggests miR-24 plays important roles in human carcinogenesis. However, its precise biological role remains largely elusive. This study examined the role of miR-24 in gastric cancer (GC).MethodsThe expression of miR-24 in GC tissues compared with matched non-tumor tissues and GC cells was detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 41 publications
3
57
1
Order By: Relevance
“…miRNAs are important regulators in the development of gastric adenocarcinoma (Duan et al, ; Kang et al, ; Shen et al, ). miR‐665 is a newly identified miRNA in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are important regulators in the development of gastric adenocarcinoma (Duan et al, ; Kang et al, ; Shen et al, ). miR‐665 is a newly identified miRNA in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-24 could promote cell proliferation in lung cancer (25) and hepatocellular carcinoma (26). However, miR-24 could inhibit cell proliferation in gastric cancer (27,28), and acts as a tumor suppressor in colon cancer (29). In breast cancer, the role of miR-24 also remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [17] showed that miR-24 is downregulated in GC tissues compared with matched nontumor tissues and that ectopic expression of miR-24 in GC cells suppressed cell proliferation, migration, and invasion in vitro as well as tumorigenicity in vivo. Furthermore, upregulation of miR-24 in terminally differentiated cells has been demonstrated [18].…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of miR-24 in GC cells suppressed cell proliferation, migration, and invasion in vitro as well as tumorigenicity in vivo [17]. The mechanisms of downregulation of miR-24 in GC have not yet been completely investigated.…”
Section: Discussionmentioning
confidence: 99%